Cognitive Uncertainty in Intertemporal Choice - Benjamin Enke; Thomas W. Graeber (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper studies the relevance of cognitive uncertainty – subjective uncertainty over one's utility-maximizing action – for understanding and predicting intertemporal choice. The main idea is that when people are cognitively noisy, such as when a decision is complex, they implicitly treat different time delays to some degree alike. By experimentally measuring and manipulating cognitive uncertainty, we document three economic implications of this idea. First, cognitive uncertainty explains various core empirical regularities, such as why people often appear very impatient, why per-period impatience is smaller over long than over short horizons, why discounting is often hyperbolic even when the present is not involved, and why choices frequently violate transitivity. Second, impatience is context-dependent: discounting is substantially more hyperbolic when the decision environment is more complex. Third, cognitive uncertainty matters for choice architecture: people who are nervous about making mistakes are twice as likely to follow expert advice to be more patient.
Keywords: 330; cognitive uncertainty; intertemporal choice; complexity